Targeting AXL cellular networks in kidney fibrosis - Grøndal, Sturla M.; Blø, Magnus; Nilsson, Linn I. H.; Rayford, Austin J.; Jackson, Akil; Gausdal, Gro; Lorens, James B. (Frontiers in Immunology, 2024)
The incidence of chronic kidney disease (CKD) is increasing, in parallel with risk factors including obesity and diabetes mellitus. AXL plays a central role in CKD, providing a rationale to evaluate clinical AXL targeting agents. To determine the efficacy and underlying molecular mechanisms of AXL inhibition in CKD, we employed a murine unilateral ureteral obstruction (UUO) model treated with a selective AXL kinase inhibitor (bemcentinib) during disease progression. Preventive treatment with bemcentinib significantly attenuated fibrosis in the UUO model. The anti-fibrotic effect correlated with a decrease in mesangial cells and inhibition of innate immune cell infiltration, while the proportion of epithelial cells increased. We mapped AXL expression to a unique network of cells in the kidney: mesangial cells, pericytes, macrophages and dendritic cells. We propose that AXL targeting affects an important cellular interaction network underlying fibrotic progression. These results support the clinical application of AXL targeting agents to treat CKD.